Knowledge, attitude and practices regarding breastfeeding and infant milk substitutes among mothers of upper middle-class society in a baby friendly hospital initiative accredited hospital of New Delhi, India - Gangwal, Maansi; Nair, Bindu T.; Singh, Varun Kumar (International Journal of Contemporary Pediatrics, 2019)
Background: Exclusive breastfeeding is considered a major public health intervention to promote both child and maternal health. Introduction and awareness of infant milk substitutes among mothers appear as a threat to this important practice. Methods: The study is an observational cross-sectional study using a questionnaire containing socio-demographic variables. The study was conducted among 300 mothers who reported to immunization clinic and paediatrics OPD of a BFHI accredited hospital in Delhi. Data collected in the study has been analysed using SPSS version 21.0 and MS-Excel. Student ‘t’ test for quantitative variables and ‘chi square test’ for categorical variable have been used for statistical significance. p-value <0.05 was considered to be significant. Results: In this study 78.7% mothers intended to breastfeed. 71.3% knew that breastfeeding should be continued up to 2 years and 96.3% knew exclusive breastfeed should be given till 6months. Major source of knowledge were doctors and elders of society. However, 49.6% mothers started breastmilk substitutes before 6 months of age. Major causes that appeared as barriers against exclusive breastfeeding were insufficient quantity of milk (23.4%), child refusal (61%) and maternal health problems (15.6%). Conclusions: Despite good knowledge about breastfeeding among upper middle-class mothers, practice of exclusive breastfeeding remains suboptimal. There is a need for more reinforcement upon importance of breastfeeding, its benefits for both mother and baby so as to foster the practice.